A Survey Investigating Alfalfa Winter Injury in Minnesota and Wisconsin from the Winter of 2012‐2013. Issue 1 (1st December 2014) - Wells, M. Scott; Martinson, Krishona L.; Undersander, Daniel J.; Sheaffer, Craig C.
Abstract : The climate in the upper Midwest is noted for extreme weather events that greatly increase the risk of alfalfa ( Medicago sativa L.) winter injury. An electronic survey was sent to alfalfa producers and crop consultants in Minnesota, Wisconsin, and Iowa with the goal of providing a retrospective assessment of the causes of alfalfa winter injury during the winter of 2012–2013. Almost all alfalfa producers who responded to the survey observed some winter injury, and a majority of crop consultants indicated more than 2001 acres had been affected in among their clients. A majority of crop consultants and alfalfa producers indicated that they perceived that freezing rain during the winter of 2013 combined with the dry fall of 2012 and the lack of snow cover caused alfalfa winter injury. Along with weather events, management practices also affected the incidence of alfalfa winter injury, with the lowest occurrences of winter injury observed in fields that had 13 or more inches of alfalfa regrowth. The results from the survey confirm that alfalfa winter injury was probably caused by a combination of weather events and management decisions.